AUTOMATED PERSONALITY PREDICTIVE MODEL FOR E-RECRUITMENT USING LOGISTIC REGRESSION TECHNIQUE - Omotosho, Oluyinka I (IJRDO -Journal of Computer Science Engineering, 2023)
Human personality plays a vital role in individual’s life as well as in the development of an organization. Common ways to evaluating human personality is by using standard questionnaires or by analyzing the Curriculum Vitae (CV). Traditionally, recruiters manually shortlist/filters a candidate’s CV as per their requirements. In this work, a system that automates the eligibility check and aptitude evaluation of candidates in a recruitment process is developed. To meet this need an automated system module is developed for the analysis of aptitude or personality test based on candidate’s CV. The work presented in this paper determines the personality trait of applicants through CV analysis using Python upon which the Personality prediction Model is built. The result helps in evaluating the qualities in the candidates by analyzing personality trait and character of such candidate. The system provides serves as a better option for the recruitment process so that candidate’s data can extracted from CV and shortlisted for the best decision via fair judgment.